New detector based on composite of carbon nanotubes with nanoparticles of cobalt oxide for carbohydrates analysis by HPLC with reverse pulsed amperometric detection - De Sá, Acelino C. [UNESP]; Paim, Leonardo L. [UNESP]; Stradiotto, Nelson R. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2020)
This work aims to present an alternative detector for the determination of arabinose, galactose, glucose and xylose in hydrolyzed sugarcane bagasse. The detector was developed using an electrode modified with multi-walled carbon nanotubes containing cobalt oxide nanoparticles (GCE/MWCNT/CoOOH) applied in high-performance liquid chromatography (HPLC) with reverse pulsed amperometric detection (RPAD). The limits of detection obtained were 3.4 × 10-6, 4.4 × 10-6, 3.6 × 10-6 and 5.0 × 10-6 mol L-1 for arabinose, galactose, glucose and xylose, respectively. The standard addition method was used to determine the concentration of sugars in the hydrolyzed sugarcane. The determined concentrations for arabinose, galactose, glucose, and xylose were 1.0 × 10-3, 7.2 × 10-5, 3.0 × 10-3 and 2.4 × 10-3 mol L-1, respectively. The results demonstrate that this new method can be used for the detection of sugars without the interference of other electroactive species.
Keywords: Carbon nanotubes; Cobalt oxide nanoparticles; HPLC-RPAD; Second generation ethanol; Sugarcane bagasse